Effects of 4 week endurance training on PGC-1α expression in adipose tissue, ANGPTL8 serum concentrations and beta cells function of STZ diabetic rats - Hamid Reza Sadeghipour; Mohsen Salesi; Alireza Rabiezade (Fasa University of Medical Sciences, 2018)
Background & Objective: Angiopoietin-like Proteins 8 (ANGPTL8) which secreted form adipose tissue due to downstream PGC-1α pathways, is the main factor for regeneration of beta cell. The aim of this study was to investigate the effect of 4 endurance training program on PGC-1α expression in adipose tissue, ANGPTL8 serum concentration and beta cell function (HOMA.B) in diabetic rats. Materials & methods: Male Wistar rats (N=24) divided in 3 groups include healthy control (HC), diabetic control (DC) and endurance training (ET). After induction of diabetes with STZ, training groups performed 4 weeks endurance training and real-time polymerase chain reaction (Real-Time PCR) method used for the relative expression of PGC-1α in visceral adipose tissue, the enzyme-linked immunosorbent assay (ELISA) method for measuring serum ANGPTL8 levels. Also beta cell number was counted with pancreases hematoxylin-eosin evaluation. Results analyzed with ANOVA. Results: The relative expression of mRNA PGC-1α was significantly increased in ET (P=0.001). Although ANGPTL8 levels increased in ET group, this change wasn't significant (P=0.47). HOMA.B didn't showed any significant change in ET (P=.0.08) but the number of beta cells in this group significantly increased (P=0.001). There was a positive correlation between relative mRNA PGC-1α and ANGPTL8 levels. Conclusion: Despite the positive and significant correlation between relative expression of mRNA PGC-1α and ANGPTL8, this increase wasn't significant, but this could increases the number of beta cell in endurance training group. Further studies with differences training programs are recommended.